RF and microwave reconfigurable bandpass filter design using optimized active inductor circuit. Issue 9 (9th October 2018) - Ben Hammadi, Aymen; Haddad, Fayrouz; Mhiri, Mongia; Saad, Sehmi; Besbes, Kamel
Abstract: In this article, a design methodology of an active bandpass filter (BPF) using tunable active inductor (TAI) achieving wide frequency contiguous tuning range (FTR) is presented. The tunable BPF is realized with a differential TAI (DTAI) employing two‐reconfiguration mechanisms one for coarse‐tuning using a controllable current source while the fine‐tuning is performed through a variable feedback resistance. The center frequency tuning is performed through the variation of the DTAI control voltages. A cross‐coupled pair based negative resistance technique is also applied to compensate the resistive losses of equivalent RLC resonator. The filter performances are significantly improved using several optimization techniques such as voltage scaling and multigate finger techniques. The proposed BPF is simulated using 0.13 μm CMOS technology. The filter achieves an insertion loss (IL) of 26.62‐33.45 dB over the tuning range 1.16‐3.27 GHz with a relative bandwidth of 1.3%‐3.4%. The noise figure and input 1‐dB compression point at 1.84 GHz are 14.93 dB and 2.72 dBm, respectively. The designed RF filter consumes an average power of 5 mW at 1 V supply voltage.